1000 trees planted to fight against global warming - UMP, PNC (2018)
Pekan, 5 September - Nations around the world are upping their game in the fight against climate change, so as Universiti Malaysia Pahang (UMP), UMP have manage to pull the crowd of 1000 new students to plant sapling to combat the effect of global warming. Sapling from Kelat Jambu Laut and Ketapang species were planted at Laman Cendekia, under the myTREEvolution Integrated CSR project.